GLOBAL HEALTH AND JUSTICE - JAMES DWYER (Bioethics Volume 19 Numbers 5-6 2005, 2005)
In Australia, Japan, Sweden, and Switzerland, the average life expectancy is now greater than 80 years. But in Angola, Malawi, Sierra Leone, and Zimbabwe, the average life expectancy is less than 40 years. The situation is even worse than these statistics suggest because average figures tend to mask inequalities within countries. What are we to make of a world with such unequal health prospects? What does justice demand in terms of global health? To address these questions, I characterize justice at the local level, at the domestic or social level, and at the international or global level. Because social conditions, structures, and institutions have such a profound influence on the health of populations, I begin by focusing attention on the relationship between social justice and health prospects. Then I go on to discuss health prospects and the problem of global justice. Here I distinguish two views: a cosmopolitan view and a political view of global justice. In my account of global justice, I modify and use the political view that John Rawls developed in The Law of Peoples . I try to show why an adequate political account must include three duties: a duty not to harm, a duty to reconstruct international arrangements, and a duty to assist.